Characterization Of Thermoelectric For Energy Harvesting On Low-Level Heat Sources - Abdal Kadhim, Ali Mohammed; Kok, Swee Leong (Centre For Advanced Research On Energy (UTeM), 2017)
Electric power harvesting from thermal energy using thermoelectric (TE) has been getting popular as a potential electrical energy source to replace batteries due to its direct current output. The focus of this paper is on the investigation of low level thermal energy below 150C that generated from electronic devices and mechanical machinery, and using TE’s to convert the heat energy, which normally treated as wasted energy into a useful amount of electrical power to power up portable low power electronic devices. For this study, the TE module is subjected to a range of heat source using heating element that resemble the real temperature that generated from the real electronic devices and mechanical machinery. The quantity of harvested electrical power was reported. From the experimental results it can be observe that the voltage output is linearity proportion to the applied heat gradient on the TE faces. At a temperature gradient of 60 C, a voltage output of 4 V is measured. The voltage output can be increased by stacking the TE on top of each other, from 0.067V/ C for 1 TE to 0.093V/ C for 4 TE.